A proposal for coherent nomenclature of multicomponent crystals. Issue 1 (11th February 2019) - Gryl, Marlena; Kozieł, Marcin; Stadnicka, Katarzyna M.
Abstract : A new, systematic, unambiguous and unified nomenclature applicable for co‐crystals and other multicomponent solid materials is presented. Abstract : Here a new, systematic, unambiguous and unified nomenclature for multicomponent materials is presented. The approach simplifies naming schemes of extraordinary co‐crystals containing multiple building blocks with different charges. Although the presented examples of cytosine compounds cannot cover all possibilities, they clearly show that the new nomenclature is flexible and can be easily extended to other multicomponent materials.